PENGARUH MEDIA SOSIAL, DESAIN KONTEN PEMASARAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK LOKAL OLEH MILENIAL DI ACEH TENGGARA - Ayu Ara; Sabitah Sabitah; Muridha Hasan (CV. Armas Suan Sejahtera, 2025)
This study examines the influence of social media, marketing content design, and price perception on the purchasing decisions of local products among millennials in Aceh Tenggara Regency. The research is motivated by the increasing role of digital technology and social media in shaping consumer behavior, particularly among millennials, who show a strong preference for engaging, informative, and visually appealing digital content. Understanding how these factors affect purchasing decisions is critical for local businesses seeking to enhance their competitiveness in the digital marketplace. This research employs a quantitative approach using a survey method, distributing structured questionnaires to 100 millennial respondents aged 20–35 years who have previously purchased local products. Data collected were analyzed using multiple linear regression to determine both the partial and simultaneous effects of the three independent variables on purchasing decisions. The results reveal that social media, marketing content design, and price perception significantly influence the buying decisions of millennials, both individually and collectively. These findings suggest that local SMEs can enhance consumer interest and loyalty by leveraging effective digital marketing strategies, including creative content presentation and appropriate pricing policies. Furthermore, the study provides insights for regional governments to support adaptive promotional initiatives that strengthen local product visibility and competitiveness in the digital era. This research contributes to the understanding of millennial consumer behavior and practical marketing strategies for local product development.